AI DAN DILEMA BERPIKIR: KEMAJUAN INTELEKTUAL ATAU KEMUNDURAN KRITIS? - Mohamad Akbar; Sudadi; Bahrani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article examines the dialectical relationship between the development of artificial intelligence (AI) and human critical thinking capacity in the era of digital transformation. AI, evolving at an exponential pace, has fundamentally altered how humans process information, make decisions, and construct knowledge. On one hand, AI offers an acceleration of human cognitive capacity through intellectual augmentation; on the other, excessive dependence on AI poses serious risks to independent, reflective, and critical thinking. Using a library research approach with critical analysis of recent academic sources and foundational texts, this article examines four main dimensions: (1) AI's impact on human cognitive architecture; (2) the relationship between AI use and critical thinking development; (3) critical education perspectives on AI's cognitive threats; and (4) recommendations for building a balance between AI utilization and the preservation of critical thinking capacity. The findings indicate that AI has the potential to be an extraordinary instrument of intellectual progress as well as a latent threat to human cognitive autonomy, depending on whether humans position themselves as passive users or as critical and reflective agents.